The RhinoCEROS Guidelines: A Practical Tool for Reporting Nasal Anatomy on Computed Tomography Pertaining to Rhinoplasty - McIntosh, Cameron; Stutterheim, James; Prinsloo, Hendrick; Randall, Michael; Toman, Julia; Pisapia, Francesco (Facial Plastic Surgery, 2023)
Cone-beam computed tomography (CT) is gaining popularity worldwide due to an increasingly diffuse and affordable in-office availability. It is becoming more commonplace for rhinoplasty surgeons to utilize this imaging as tool for preoperative assessment; however, there is inconsistency among radiologists commenting on specific structures of the nose or nasal cavity as there is currently no standardized reporting protocol. The goal of this article is to present clear guidelines for radiologists to report relevant nasal anatomy in the context of preoperative rhinoplasty evaluation. We have proposed the RhinoCEROS Guidelines, which stands for: Rhinoplasty Cephalometric Evaluation for Radiologic pre-Operative Systematization. This guideline highlights the primary aspects of nasal anatomy on CT that affect rhinoplasty outcomes and will provide radiologists with a straightforward template for reporting this increasingly popular use for CT scan.
Keywords: cone-beam CT; rhinoplasty; preoperative planning